2019
DOI: 10.1186/s41072-019-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

A cointegrating stock trading strategy: application to listed tanker shipping companies

Abstract: In the current paper, we propose a strategy to trade a portfolio of listed shipping companies in the US market. In particular, we estimate a co-integrating relationship between the weekly stock market returns of a portfolio of tanker shipping companies and the Baltic Tanker Index, exploiting the close relationship between freight rates and the stock market performance of shipping companies. Our results suggest that a trading strategy on the basis of a co-integrating relationship and a simple moving average rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…More recently, Alizadeh and Nomikos (2007) employed a dataset of monthly data for 28 years and showed that co-integrating techniques can be more useful for shipping investors, again showcasing that fundamentals play an important role. These results are complemented by Michail and Melas (2019), who showed that a co-integrating technique based on fundamentals is also useful for stock trading purposes.…”
Section: Literature Reviewmentioning
confidence: 82%
“…More recently, Alizadeh and Nomikos (2007) employed a dataset of monthly data for 28 years and showed that co-integrating techniques can be more useful for shipping investors, again showcasing that fundamentals play an important role. These results are complemented by Michail and Melas (2019), who showed that a co-integrating technique based on fundamentals is also useful for stock trading purposes.…”
Section: Literature Reviewmentioning
confidence: 82%
“…In December 2019, the coronavirus disease, or COVID-19, first emerged in China and, by July 2021, had quickly spread to 220 countries, infecting over 188 million people [52]. Most governments implemented lockdowns of various intensities in response [53]. The volume of cargo transported by sea shrunk considerably to halt the spread of the virus in vessels and at ports [54].…”
Section: Covid-19mentioning
confidence: 99%
“…Few studies have investigated the specific reactions of the shipping industry to these events. Michail and Melas [53] examined how much the COVID 19 pandemic affected the shipping industry for the freight rates of tankers and bulk shipping vessels.…”
Section: Covid-19mentioning
confidence: 99%